DEVELOPING CHARACTER BASED LESSON PLANS FOR THE TENTH GRADE STUDENTS OF VOCATIONAL SCHOOL (SMK) - Putra, B.M (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2018)
This study was a Research and Development study (R&D) used Sugiyono?s model which aimed at identifying problem and the needs of the lesson plans in SMK Triatma Jaya Singaraja, determining the suitable design and developing character based lesson plan in SMK Triatma Jaya, measuring the effectiveness and the quality of the lesson plan developed. The data of the present study were analyzed descriptively and quantitatively. This result showed that the existing lesson plans did not clearly state the values of nation character and the assessment and it was not explicitly stated on the learning activity. The learning activity seemed monotone. There seemed to be materials repetition. The materials must be suitable with the students? department. The lesson plans developed were designed based on technical guideline of lesson plan development proposed by Board Directors of Senior High School Development (2010) with character assessment as an addition. The lesson plans were developed in form of integrated lesson plan. The lesson plans developed were effective and the quality is excellent.